A Computational Study on the Use of an Aluminium Metal Matrix Composite and Aramid as Alternative Brake Disc and Brake Pad Material. (26th August 2014) - Idusuyi, Nosa; Babajide, Ijeoma; Ajayi, Oluwaseun. K.; Olugasa, Temilola. T.
Abstract : A computational model for the heat generation and dissipation in a disk brake during braking and the following release period has been formulated. The model simulates the braking action by investigating the thermal behaviour occurring on the disc and pad surfaces during this period. A comparative study was made between grey cast iron (GCI), asbestos, Aluminium metal matrix composite (AMC), and aramid as brake pad and disc materials. The braking process and following release period were simulated for four material combinations, GCI disc and Asbestos pad, GCI disc and Aramid pad, AMC disc and Asbestos pad, AMC disc and Aramid pad using COMSOL Multiphysics software. The results show similarity in thermal behaviour at the contact surface for the asbestos and aramid brake pad materials with a temperature difference of 1.8 K after 10 seconds. For the brake disc materials, the thermal behaviour was close, with the highest temperature difference being 9.6 K. The GCI had a peak temperature of 489 K at 1.2 seconds and AMC was 465.5 K but cooling to 406.4 K at 10 seconds, while the GCI was 394.7 K.